A genome-wide association study of pulmonary tuberculosis in Morocco - Grant, A. V. (Hum Genet, 2016)
Although epidemiological evidence suggests a human genetic basis of pulmonary tuberculosis (PTB) susceptibility, the identification of specific genes and alleles influencing PTB risk has proven to be difficult. Previous genome-wide association (GWA) studies have identified only three novel loci with modest effect sizes in sub-Saharan African and Russian populations. We performed a GWA study of 550,352 autosomal SNPs in a family-based discovery Moroccan sample (on the full population and on the subset with PTB diagnosis at <25 years), which identified 143 SNPs with p < 1 × 10(−4). The replication study in an independent case/control sample identified four SNPs displaying a p < 0.01 implicating the same risk allele. In the combined sample including 556 PTB subjects and 650 controls these four SNPs showed suggestive association (2 × 10(−6) < p < 4 × 10(−5)): rs358793 and rs17590261 were intergenic, while rs6786408 and rs916943 were located in introns of FOXP1 and AGMO, respectively. Both genes are involved in the function of macrophages, which are the site of latency and reactivation of Mycobacterium tuberculosis. The most significant finding (p = 2 × 10(−6)) was obtained for the AGMO SNP in an early (<25 years) age-at-onset subset, confirming the importance of considering age-at-onset to decipher the genetic basis of PTB. Although only suggestive, these findings highlight several avenues for future research in the human genetics of PTB.